Specification for copper and copper alloys plate (BSI, 1969)
Copper, Copper alloys, Sheet materials, Chemical composition, Dimensional tolerances, Test specimens, Testing conditions, Bend testing, Splitting tests, Weight tolerances, Density, Thickness, Tensile strength, Elongation, Gas-resistance tests, Hydrogen, Brittleness, High-temperature testing, Embrittlement